Pemetaan Faktor Sosial-Ekonomi Penyebab Stunting di Kabupaten Aceh Timur - Puti Andiny; Afrah Junita; Tuti Meutia; Umi Sefiana Barokatul Aulia (Jurnal Penelitian Ekonomi Akuntansi, 2024)
The objective of the research is to identify and map socioeconomic factors that influence stunting rates in children in East Aceh Regency. The analytical method utilized is descriptive qualitative, utilizing interview techniques. The interviewees for this study were nutrition officers from community health centers located in each sub-district of East Aceh Regency. According to the study's findings, the factors that contribute to stunting are 1) a lack of parental understanding of the risk of stunting and the period of the First 1000 Days of Life, which has an impact on poor consumption patterns during pregnancy and parenting patterns for children, 2) family economic factors or low income levels among parents, and 3) a lack of access to health services. The limitation of this research is that researchers were unable to access all community health centers in East Aceh Regency due to logistical problems. It is hoped that future researchers would be able to conduct study in all health facilities in every sub-district of East Aceh Regency in order to create a map of the causes that cause stunting, which will be valuable in developing appropriate strategies for conquering stunting in the region